The Effect of Artificial Intelligence (Microbit) in Raising the Motivation Towards Learning Programming Among the Students of Educational Technology at King Abdulaziz University in Jeddah - Al-Qarni, Samaher Ahmed; Omran, Amani Mohammed (Journal of Educational and Psychological Sciences, 2021)
The research seeks to know the effect of Artificial Intelligence (Microbit) in raising the motivation towards learning programming among the students of educational technology at King Abdulaziz University in Jeddah. The sample consisted of (14) students, and the research followed the quasi-experimental method for one experimental group. Also, a pre-measurement and post-measurement was done by using the motivation measure towards learning programming. The results of the research confirmed that there were statistically significant differences at the level of significance (0.001) between the results of students for their motivation towards learning programming before and after the use of the (Microbit) in favor of post-measurement. The research also recommended the importance of employing artificial intelligence techniques in curricula and academic projects for its effective role in making the education process active, improving the performance of male and female students and raising their motivation. As well as, preparing educational institutions and centers, and training teachers to work using artificial intelligence techniques, especially the Microbit device.
Keywords: Motivation; Artificial Intelligence; Microbit